SPIRITUAL THREATS AND THE NEED TO PREVENT THEM - Ulugbek Saliev (European Journal of Interdisciplinary Research and Development, 2023)
Today, when glabalization processes are gaining momentum, ideological, ideological, spiritual threats remain one of the greatest risks to the future of our country. Today, when the achievements of Science, Technology are developing, such threats are becoming more dangerous. Inability to perceive or ignore ideological, ideological, spiritual threats in a timely manner can lead to situations in which it is difficult to correct.